KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN IMB (Izin Mendirikan Bangunan) DI DPMPTSP KOTA CIMAHI - Fadlan Karunia Hidayat; Fazri Miftahuddin; Dendi Herdiansyah; Irfan Sholihin; Roziana Lahmini (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2019)
Public service is fulfilling the needs and needs of the community by state administrators. IMB in Cimahi City DPMPTSP, using qualitative research methods, qualitative research conducted related to researchers want to know the phenomenon that cannot be quantified that discusses research on how to work, understanding of information that varies, characteristics of goods and services, cultural procedures, and others so. Qualitative research methods are conducted by interviewing the subject. The results of this study indicate that in Cimahi DPMPTSP there are a number of problems relating to communities that do not have technical requirements and documents, Cimahi's DPMPTSP program to improve services related to socialization for the community selected for each sub-district, in accordance with building permits (IMB) , the background of Cimahi's DPMPTSP socialization was because the people who only knew of building a building and without being equipped with an IMB letter.